SARS‐CoV‐2 IgG "heritage" in newborn: A credit of maternal natural infection. Issue 1 (19th September 2022) - Marchi, Laura; Vidiri, Annalisa; Fera, Emanuele Arturo; Pallottini, Marta; Perelli, Federica; Gardelli, Monica; Brunelli, Tamara; Poggetto, Paolo Dal; Martelli, Elena; Straface, Gianluca; Signore, Fabrizio; Fusco, Ismaele; et al.
Abstract: Description of transplacental passage of specific SARS‐CoV‐2 IgG from mothers who contracted natural infection to their newborns. Retrospective cohort analysis including pregnant women diagnosed with SARS‐CoV‐2 and their newborns both tested for SARS‐CoV‐2 specific IgG and IgM with antibody titration at delivery. Nasopharyngeal swab were taken from both mothers and neonates, and tested for SARS‐CoV‐2 using polymerase chain reaction (PCR). IgM and IgG were analyzed in maternal and neonatal serum of 143 mother−infant dyads. 86% of women with a positive SARS‐CoV‐2 PCR >14 days before delivery developed specific IgG and 84% of their infants showed transplacental passage of IgG. Pregnant women infected with SARS‐CoV‐2 achieve antibody seroconversion following the kinetics described in the general population, and transplacental transfer of IgG specific antibodies occurs. No conclusion can be drawn on passive immunity efficacy or duration.